From the traditional lecture to the MOOC: twelve years of evolution of a subject about web application programming - Sergio Luján-Mora (Red U, 2013)
This paper shows the evolution of the teaching of a course of a computer engineering degree, "Internet Programming", over twelve years. In this course, students learn the technologies and methods used in web application development. Over the past twelve years, the teaching method in the course has been changed more or less in a natural way. During the first years of "Internet Programming", the traditional lecture was used as the teaching method. Although students‘ learning outcome was not bad, among teachers there was a feeling that it could be done better. In the following years, there were some experiments with other teaching methods until the last year, in which the inverted classroom (flip teaching) method was used together with a Massive Open Online Course (MOOC). The use of this teaching method offers two important advantages. On the one hand, the time in the classroom can be used to do active learning activities in which teachers' role is essential. On the other hand, students can review learning materials at their own pace.